Development of polybenzimidazole-based proton exchange membrane for fuel cell applications - Ong, Guan Jie (2015)
The main aim of this project is to synthesize Polybenzimidazole (PBI) and then use the PBI synthesized to develop a proton exchange membrane suited to be used as a membrane electrolyte in High Temperature – Proton Exchange Membrane Fuel Cell (HT-PEMFC) applications. Successful synthesis of PBI was achieved through a polycondensation process and PBI membranes were casted. Membrane characterisation tests such as Fourier Transform Infrared Spectroscopy (FTIR) test, membrane acid uptake, tensile strength test and proton conductivity test were then conducted to determine the chemical composition, mechanical properties and electrochemical properties of the PBI membranes, with references made to the membranes casted from commercially available PBI. Results have shown that the chemical composition of the PBI synthesized were similar to that of commercially available PBI. Another key observation made is that the acid doping level of a PBI membrane is a key parameter in determining the mechanical and electrochemical properties of a PBI membrane. In general, at low acid doping levels, it leads to an increase in both the proton conductivity and the tensile strength of the PBI membrane. However, if the acid doping level is high, it may lead to a deterioration of the PBI membrane’s tensile strength while the proton conductivity of the PBI membrane is further enhanced. A right amount of acid doping level in a PBI membrane must be selected to achieve the optimal performance of a HT-PEMFC.